2012
DOI: 10.1159/000337220
|View full text |Cite
|
Sign up to set email alerts
|

Rise to Power: A Case Study of Male Fecal Androgen and Cortisol Levels before and after a Non-Aggressive Rank Change in a Group of Wild White-Faced Capuchins (Cebus capucinus)

Abstract: We examined fecal androgen and cortisol levels in three adult male white-faced capuchin monkeys (Cebus capucinus) before and after a non-aggressive rank increase in one habituated group residing in the Santa Rosa Sector of the Área de Conservación Guanacaste, Costa Rica. Fecal samples (n = 116) were collected opportunistically between July 2006 and July 2007. Alpha males had higher mean androgen levels than subordinates, and acquisition of the alpha position was linked to an immediate increase in mean androgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…However, prior studies from this population of C. capucinus have shown that fGC levels of adult females increase in response to a presumably stressful situation (change in male group composition; Carnegie et al, 2011b). Additionally, individual fGC levels increase with a rise in male dominance rank (Schoof et al, 2011) and decrease with increased habituation levels (Jack et al, 2008), both situations presumably associated with changes in stress. ACTH challenge in the closely related robust tufted capuchin, Sapajus (Cebus) apella , results in a cortisol increase (Torres-Farfan et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, prior studies from this population of C. capucinus have shown that fGC levels of adult females increase in response to a presumably stressful situation (change in male group composition; Carnegie et al, 2011b). Additionally, individual fGC levels increase with a rise in male dominance rank (Schoof et al, 2011) and decrease with increased habituation levels (Jack et al, 2008), both situations presumably associated with changes in stress. ACTH challenge in the closely related robust tufted capuchin, Sapajus (Cebus) apella , results in a cortisol increase (Torres-Farfan et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, this phenomenon has not been investigated or documented in male primates, though evidence to date clearly demonstrates that T levels vary throughout a male’s life. Additionally, variability in individual T levels has been documented among adult male primates according to ecological seasonality (e.g., Cerda-Molina et al, 2009; Gesquiere et al, 2011a; but see Strier et al, 1999), mating/breeding seasonality (Bales et al, 2006; Brockman et al, 1998; Girard-Buttoz et al, 2009; Gould and Ziegler, 2007; Lynch et al, 2002; Ostner et al, 2002; Ostner et al, 2011; but see Strier et al, 1999; see Place and Kenagy, 2000 for review of non-primates), group demography (Rangel-Negrín et al, 2011), dominance status (Arlet et al, 2011; Kraus et al, 1999; Muehlenbein et al, 2004; Muller and Wrangham, 2004a; Muroyama et al, 2007; Schoof and Jack, 2013; Setchell et al, 2008), and changes in dominance status (Alberts et al, 1992; Beehner et al, 2006; Brockman et al, 1998; Eberhardt et al, 1980; Mendoza et al, 1979; Rose et al, 1975; Schoof et al, 2011; Setchell and Dixson 2001a; Wickings and Dixson, 1992). …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations